The applicability of the risk score approach to competitive sport: Development of a physical success score for the Canadian Football League combine - Matsuo, H.; Funasaki, K.; Yamada, S. (The Journal of Strength and Conditioning Research, 2022)
In the scouting combine of the Canadian Football League (CFL), players are measured for 6 athletic abilities, including 2 measurements of body size. For coaches and their players who desire to play in the CFL, knowing the players metrics that are important for being drafted and their levels will help coaches plan and evaluate their training. Thus, the purpose of this study was to provide a simple scoring system using the predictors of CFL Combines identified by multivariate analysis and their regression coefficients, and reference values. In this study, authors created a scoring system to classify draft success and failure of CFL Combines based on the measurement results. This scoring system was named as the physical success score (PSS). To do so, a repeated grid-search cross-validation for variable selection algorithm was performed on the players (line: n = 211, big skill linebacker, running back and tight end: n = 177, skill [defensive back and wide receiver]: n = 231) who participated in the CFL Combines between 2011 and 2019. The final binary logistic regression models and the reference values were used to generate the PSS for each group. As a result, PSS of the line, big skill, and skill were developed. In each group, all possible total scores and the estimated draft success probability were shown. From the results of this study, it was concluded that the PSS approach can provide useful information for coaches in setting training goals.